2019
DOI: 10.1111/1751-7915.13458
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence‐based analysis of the intracytoplasmic membranes of type I methanotrophs

Abstract: Summary Most methanotrophic bacteria maintain intracytoplasmic membranes which house the methane‐oxidizing enzyme, particulate methane monooxygenase. Previous studies have primarily used transmission electron microscopy or cryo‐electron microscopy to look at the structure of these membranes or lipid extraction methods to determine the per cent of cell dry weight composed of lipids. We show an alternative approach using lipophilic membrane probes and other fluorescent dyes to assess the extent of intracytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…The direct coupling mechanism consists on the fact that the same redox cofactor co‐oxidized with methane, is responsible for the further oxidation of methanol to formaldehyde. Particulate methane monooxygenases (pMMOs), are located in so called intracytoplasmic membranes, recent fluorescence based experiments (Whiddon, Gudneppanavar, Hammer, West, & Konopka, 2019) have shown that these structures are connected to the cytoplasmic membrane, therefore redox carriers such as cytochromes, can be potentially exchanged between pMMOs and the respiratory chain. The direct coupling mechanism of methane oxidation allows M. alcaliphilum to obtain higher biomass yields on methane than those potentially achievable by type II methanotrophs such as bacteria from the genus Methylocystis (Bordel, Rodríguez, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The direct coupling mechanism consists on the fact that the same redox cofactor co‐oxidized with methane, is responsible for the further oxidation of methanol to formaldehyde. Particulate methane monooxygenases (pMMOs), are located in so called intracytoplasmic membranes, recent fluorescence based experiments (Whiddon, Gudneppanavar, Hammer, West, & Konopka, 2019) have shown that these structures are connected to the cytoplasmic membrane, therefore redox carriers such as cytochromes, can be potentially exchanged between pMMOs and the respiratory chain. The direct coupling mechanism of methane oxidation allows M. alcaliphilum to obtain higher biomass yields on methane than those potentially achievable by type II methanotrophs such as bacteria from the genus Methylocystis (Bordel, Rodríguez, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The ICM area as a fraction of total cell area had a median value of 5.7% in the electrode biofilm grown at -0.07 V and 4.2% in the fumarate cells, but there is a high variance in fractional area with some cells having over 30% of the area occupied by ICM (Figure S5 and Figure S6). This is lower than the cell area occupied by ICMs in methanotrophs 41 . By applying identical image analysis (ICM counting) to cells collected from different conditions, we found that a change in electron acceptor significantly affects the frequency of G. sulfurreducens cells displaying ICM (Figure 4a).…”
Section: Nsmentioning
confidence: 70%
“…ICM abundance differences-We can also identify the presence of ICM in G. sulfurreducens with confocal microscopy. A similar technique has been used to identify ICM in methanotrophs 41 . We took confocal images of fixed G. sulfurreducens biofilm cells grown at 10 different anode potentials, or from cell suspensions grown with fumarate as electron acceptor, and each image had numerous individual cells (Table S1).…”
Section: Nsmentioning
confidence: 99%
See 1 more Smart Citation
“…To accommodate such large quantities of pMMO, copper triggers the formation of intracytoplasmic membranes (ICMs) that fill the cell 11 . These methanotrophic ICMs, detected more than 50 years ago 12 , have been imaged using electron 7 , 11 , 13 , 14 and fluorescence 15 microscopies and cryo-electron tomography (cryoET) 16 , but their mechanism of biogenesis is not known. In addition, the arrangement of pMMO within the ICMs and the relationship between this environment and pMMO function remain unclear.…”
Section: Introductionmentioning
confidence: 99%